2022
DOI: 10.1038/s41416-022-02063-3
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair markers in preoperative and operative endometrial cancer samples; expression concordance and prognostic value

Abstract: Background The endometrial cancer mismatch repair (MMR) deficient subgroup is defined by loss of MSH6, MSH2, PMS2 or MLH1. We compare MMR status in paired preoperative and operative samples and investigate the prognostic impact of differential MMR protein expression levels. Methods Tumour lesions from 1058 endometrial cancer patients were immunohistochemically stained for MSH6, MSH2, PMS2 and MLH1. MMR protein expression was evaluated as loss or intact to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…The International Society of Gynecological Pathologists (ISGyP) recommends MMR/MSI status analysis (preferably with curettage or hysterectomy samples) for EC patients of all ages ( Cho et al, 2019 ). Our results were similar to those of previous studies ( Talhouk et al, 2016 ; Berg et al, 2023 ), with 27.5% and 26.7% of dMMR and MSI-H, respectively, for the curettage samples but slightly higher than the 23.8% and 22.3% for the hysterectomy samples.…”
Section: Discussionsupporting
confidence: 92%
“…The International Society of Gynecological Pathologists (ISGyP) recommends MMR/MSI status analysis (preferably with curettage or hysterectomy samples) for EC patients of all ages ( Cho et al, 2019 ). Our results were similar to those of previous studies ( Talhouk et al, 2016 ; Berg et al, 2023 ), with 27.5% and 26.7% of dMMR and MSI-H, respectively, for the curettage samples but slightly higher than the 23.8% and 22.3% for the hysterectomy samples.…”
Section: Discussionsupporting
confidence: 92%
“…Factors such as advanced age, higher grade, LVSI, and deeper myometrial invasion are utilized to predict patients at high risk for recurrence despite early stage disease. This study, and others ( 9 , 13 , 22 , 27 , 28 ), confirms that MMR deficient EC is associated negative prognostic indicators. However, we found that patients with probable MMR mutation did not differ from those with MMR proficient EC in terms of stage, grade, LVSI, and myometrial invasion.…”
Section: Discussionsupporting
confidence: 87%
“…However, even with these poor prognostic features, data regarding outcomes in EC with MMR deficiency and epigenetic MMR defects have been inconsistent (9,21). While many groups have reported on reduced recurrence free survival in EC with MMR defects others have reported that there is no effect or even an improvement in OS in these tumors (11,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we constructed classification models using surgical specimens, but it is known that there is substantial agreement regarding MMR status between endometrial curettage and hysterectomy samples. Berg et al [61] mentioned the high concordance rate that can be used not only as a value for MMR status classification in endometrial cancer but also as an independent prognostic marker before resection. Therefore, if the AI classification model could be constructed for curettage specimens, it would enable the consideration of treatment strategies at an earlier phase.…”
Section: Discussionmentioning
confidence: 99%